The affordability and obtainability of gluten-free foods for adults with coeliac disease following their withdrawal on prescription in England: a qualitative study - Crocker, H; Lewis, T; Violato, M; Peters, M (Wiley, 2023)
Background Changes to prescribing policies in England have restricted or stopped access to gluten-free food on prescription for people with coeliac disease in some geographical areas. The present study aimed to explore the impact of these changes on the affordability and obtainability of gluten-free foods for adults with coeliac disease.